PAKSA BADAN TERHADAP PENANGGUNG PAJAK DALAM PROSES PENAGIHAN PAJAK - Arfeni, Ni Ketut; Markeling, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014, 2014)
This paper entitled "Gijzeling against Tax Insurer in Tax Billing Process". The method used inthis research is normative research methods and comparative approaches. Tax laws do not onlyrecognize the existence of corporal punishment for committing criminal acts taxes, but alsoknown, a detention upon the taxpayer or the person in taxes as a consequence of theimplementation of the action forced letter. The detention upon the tax payer or the personreferred to as the "Gijzeling". Therefore, this paper will explain how hostage-taking in taxcollection occurs. In addition, this paper also explains how the influence of administrativesanctions against the taxpayer. Detention upon the tax payer or insurer is called "gijzeling". Itcan only be made to the person who does not pay off tax debts after the expiration of 14 daysfrom the date of Letter of Force informed to the tax payer. Gijzeling is conducted to the TaxPayers who have tax debts of at least Rp.100.000.000, 00 and doubted for his good faith tosettle the tax debts. The administration facts in the form of interests, penalties, or the increaseimposed on the taxpayer might be deducted or eliminated. In addition, there are reduction andelimination of administrative sanctions against the taxpayer in a variety of legislation.
Keywords: Gijzeling, Tax Insurer, Tax Billing